Association of Patients’ Knowledge on the Disease and Its Management with Indicators of Disease Severity and Individual Characteristics in Patients with Chronic Obstructive Pulmonary Disease (COPD): Results from COSYCONET 2 - Fischer C; Siakavara M; Alter P; Vogelmeier CF; Speicher T; Pott H; Watz H; Bals R; Trudzinski F; Herth F; Ficker JH; Wagner M; et al. (Patient Preference and Adherence)
Carolina Fischer,1,2 Maria Siakavara,1 Peter Alter,3 Claus Franz Vogelmeier,3 Tim Speicher,3 Hendrik Pott,4 Henrik Watz,5 Robert Bals,6,7 Franziska Trudzinski,8 Felix Herth,8 Joachim H Ficker,9 Manfred Wagner,9 Christoph Lange,10 Krista Stoycheva,10 Winfried Randerath,11 Jürgen Behr,12,13 Sebastian Fähndrich,14 Tobias Welte15 ,† Isabell Pink,15 Kathrin Kahnert,12,16 Werner Seeger,17 Stefan Kuhnert,17 Tobias Gessler,17 Nina Adaskina,18 Rudolf A Jörres1 1Institute and Outpatient Clinic for Occupational, Social and Environmental Medicine, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the German Center for Lung Research (DZL), Munich, Bavaria, Germany; 2Department of Medicine I, Division of Respiratory Diseases, School of Medicine & Klinikum rechts der Isar, Technical University of Munich, Munich, Bavaria, Germany; 3Department of Medicine, Pulmonary, Critical Care and Sleep Medicine, Philipps University of Marburg (UMR), Member of the German Center for Lung Research (DZL), Marburg, Hesse, Germany; 4Section of Airway Infections, Department of Medicine, Pulmonary and Critical Care Medicine, Philipps University of Marburg (UMR), Marburg, Hesse, Germany; 5Pulmonary Research Institute at LungenClinic Grosshansdorf, Airway Research Center North (ARCN), Member of the German Center for Lung Research (DZL), Grosshansdorf, Schlewig-Holstein, Germany; 6Department of Internal Medicine V, Pulmonology, Allergology, Critical Care Medicine, Saarland University Hospital, Homburg, Saarland, Germany; 7Helmholtz Institute for Pharmaceutical Research Saarland (HIPS), Helmholtz Centre for Infection Research (HZI), Saarland University Campus, Saarbrücken, Saarland, Germany; 8Department of Pneumology and Critical Care Medicine, Thoraxklinik, University of Heidelberg, Translational Lung Research Center Heidelberg (TLRC-H), Member of the Center for Lung Research (DZL), Heidelberg, Baden-Wuerttemberg, Germany; 9Department of Respiratory Medicine, Allergology and Sleep Medicine, Klinikum Nuremberg, Nürnberg, Bavaria, Germany; 10Clinical Infectious Diseases, Research Center Borstel, Borstel, Germany; German Center for Infection Research (DZIF), Standort Hamburg-Lübeck-Borstel-Riems, Germany; Respiratory Medicine & International Health, University of Lübeck, Lübeck, Schleswig-Holstein, Germany; 11Krankenhaus Bethanien gGmbH, Klinik für Pneumologie und Allergologie, Zentrum für Schlaf- und Beatmungsmedizin, Solingen, North-Rhine Westphalia, Germany; 12Department of Medicine V, LMU University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), German Center for Lung Research (DZL), Munich, Bavaria, Germany; 13Asklepios Fachkliniken München-Gauting, Gauting, Germany; 14Department of Pneumology, Faculty of Medicine, Medical Center, University of Freiburg, Baden-Wuerttemberg, Germany; 15Clinic for Pneumology, Hannover Medical School, Member of the German Center for Lung Research (DZL), Hannover, Lower Saxony, Germany; 16MediCenterGermering, Germering, Bavaria, Germany; 17University of Giessen and Marburg Lung Center (UGMLC), Member of the German Center for Lung Research (DZL), Justus-Liebig University Giessen, Hesse, Germany; 18CAPNETZ STIFTUNG, Hannover, Lower Saxony, Germany†Tobias We